2020
DOI: 10.1063/1.5135649
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelastic equation of state and melting of Mg metal at high pressure and high temperature

Abstract: The p-V-T equation of state of magnesium metal has been measured up to 20 GPa and 1500 K using both multianvil and opposite anvil techniques combined with synchrotron X-ray diffraction. To fit the experimental data, the model of Anderson-Grüneisen has been used with fixed parameter δ T . The 300-K bulk modulus of B 0 = 32.5(1) GPa and its first pressure derivative, B 0 ' = 3.73(2), have been obtained by fitting available data up to 20 GPa to Murnaghan equation of state. Thermal expansion at ambient pressure ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The thermal expansion data of Mg 2 Si at 0 GPa were obtained from a previous study. 21 The atomic volume of Mg at a given pressure and temperature was calculated using the equations of states of Mg. 37 The data at 11 GPa are not connected by the dashed line because the crystal structure of the HPRT phase is unknown.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The thermal expansion data of Mg 2 Si at 0 GPa were obtained from a previous study. 21 The atomic volume of Mg at a given pressure and temperature was calculated using the equations of states of Mg. 37 The data at 11 GPa are not connected by the dashed line because the crystal structure of the HPRT phase is unknown.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Pressure dependencies of molar volumes were represented using the Murnaghan approximation . Bulk moduli, their pressure derivatives, and thermal expansion coefficients for simple substances and compounds were taken from previous experimental measurements: Mg, Mg 2 C, β-Mg 2 C 3 , diamond, graphite, and liquid carbon . The data for liquid Mg were found on the basis of the p , T melting curve of magnesium. , Previous ab initio results have shown that β-Mg 2 C 3 has formation enthalpy (at 0 K) close to that of the α-Mg 2 C 3 phase; so, for the β phase, we used available thermodynamic data for the α phase at ambient pressure.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Bulk moduli, their pressure derivatives, and thermal expansion coefficients for simple substances and compounds were taken from previous experimental measurements: Mg, Mg 2 C, β-Mg 2 C 3 , diamond, graphite, and liquid carbon . The data for liquid Mg were found on the basis of the p , T melting curve of magnesium. , Previous ab initio results have shown that β-Mg 2 C 3 has formation enthalpy (at 0 K) close to that of the α-Mg 2 C 3 phase; so, for the β phase, we used available thermodynamic data for the α phase at ambient pressure. The expression G Cliquid = G graphite + 100,000 – 24.21· T was adopted from ref instead of the expression G Cliquid = G graphite + 117,369 – 24.63· T because of more reasonable agreement with the experimental melting p , T curve of graphite, which results in the liquid–graphite–diamond triple-point parameters11.2 GPa and 4140 K (instead of 12.4 GPa and 4700 K).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations